Measurement of the top quark mass with lepton plus jets final states using pp collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2018)
The mass of the top quark is measured using a sample of t (t) over bar events collected by the CMS detector using proton-proton collisions at root s = 13 TeV at the CERN LHC. Events are selected with one isolated muon or electron and at least four jets from data corresponding to an integrated luminosity of 35.9 fb(-1). For each event the mass is reconstructed from a kinematic fit of the decay products to a t (t) over bar hypothesis. Using the ideogram method, the top quark mass is determined simultaneously with an overall jet energy scale factor (JSF), constrained by the mass of the W boson in q (q) over bar' decays. The measurement is calibrated on samples simulated at next-to-leading order matched to a leadingorder parton shower. The top quark mass is found to be 172.25 +/- 0.08 (stat+JSF)+/- 0.62 (syst) GeV. The dependence of this result on the kinematic properties of the event is studied and compared to predictions of different models of t (t) over bar production, and no indications of a bias in the measurements are observed.
Keywords: PAIR